2017
DOI: 10.3892/etm.2017.5183
|View full text |Cite
|
Sign up to set email alerts
|

Role of microRNA‑26a in the diagnosis of lower extremity deep vein thrombosis in patients with bone trauma

Abstract: Abstract. The present study aimed to investigate the role and mechanism of action of microRNA (miR)-26a in deep vein thrombosis (DVT). Peripheral blood was collected from 45 patients with DVT and 40 healthy controls. Levels of miR-26a, chemokine C-C motif ligand (CCL)2 mRNA and CCL7 mRNA were detected using reverse transcription-quantitative polymerase chain reaction and the value of miR-26a in the clinical diagnosis of DVT was assessed using receiver operating characteristic curve analysis. The correlation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…In recent decades, a number of miRNAs have been confirmed and characterized in human diseases, and there were many researchers who have proven that miRNAs were related to the development of SONFH, such as miR-708 [9] and miR-27a [10]. As one of the miRNAs, miR-26a was found to be associated with several kinds of human diseases, such as osteosarcoma [11,12], bone trauma [13] and osteoarthritis of knee joints [14]. Moreover, enhancer of zeste homologue 2 (EZH2) is a catalytic subunit of polycomb repressive complex 2, which is implicated in restraining the expression of gene by methylated histone H3 on lysine 27 [15].…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, a number of miRNAs have been confirmed and characterized in human diseases, and there were many researchers who have proven that miRNAs were related to the development of SONFH, such as miR-708 [9] and miR-27a [10]. As one of the miRNAs, miR-26a was found to be associated with several kinds of human diseases, such as osteosarcoma [11,12], bone trauma [13] and osteoarthritis of knee joints [14]. Moreover, enhancer of zeste homologue 2 (EZH2) is a catalytic subunit of polycomb repressive complex 2, which is implicated in restraining the expression of gene by methylated histone H3 on lysine 27 [15].…”
Section: Introductionmentioning
confidence: 99%
“…Although the Society of Interventional Radiology and the Society for Vascular Surgery has published quality improvement guidelines for the treatment of LEDVT and a relatively large amount of studies have reported a series of treatment options, no effective pharmacological methods that prevent thrombus-related damage to the vein wall in order to diminish the risk have been discovered [ 6 ]. It is common knowledge that inflammation is a major risk factor of LEDVT as levels of inflammatory cytokines are found to have increased in the peripheral blood of patients diagnosed with LEDVT [ 7 ]. Some microRNAs (miRs) have been proven to participate in inflammation activity along with having reports of acting as both prognostic and diagnostic indicators as well as the potential therapies in LEDVT [ 7–9 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is common knowledge that inflammation is a major risk factor of LEDVT as levels of inflammatory cytokines are found to have increased in the peripheral blood of patients diagnosed with LEDVT [ 7 ]. Some microRNAs (miRs) have been proven to participate in inflammation activity along with having reports of acting as both prognostic and diagnostic indicators as well as the potential therapies in LEDVT [ 7–9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In two other studies by Zhou et al (2016) [47] and Liu et al (2018) [48], plasma expression levels of miR-28-3p and miR-221 were shown to be upregulated in PE patients compared to healthy controls. In studies in which the expression of a specific miRNA was examined, levels of miR-26a [49] were found to be downregulated, whereas levels of miR-27a, miR-27b, miR-320a, and miR-320b were upregulated [50,51] in PE and DVT patients as described in Table 2. Table 1 for literature references).…”
Section: Epidemiological Studies: Mirnas and Venous Thromboembolismmentioning
confidence: 99%
“…In two other studies by Zhou et al (2016) [47] and Liu et al (2018) [48], plasma expression levels of miR-28-3p and miR-221 were shown to be upregulated in PE patients compared to healthy controls. In studies in which the expression of a specific miRNA was examined, levels of miR-26a [49] were found to be downregulated, whereas levels of miR-27a, miR-27b, miR-320a, and miR-320b were upregulated [50,51] in PE and DVT patients as described in Table 2. Of note, some studies used epidemiological and experimental approaches in their analysis. For instance, Sahu et al (2017) [27] searched for differentially expressed miRNAs in a rat model of DVT using inferior vena cava (IVC) ligation (IVC stasis model) and control animals and found that miR-145 was significantly downregulated in experimental DVT.…”
Section: Epidemiological Studies: Mirnas and Venous Thromboembolismmentioning
confidence: 99%